PERBANDINGAN GUGATAN SEDERHANA DI INDONESIA DAN BRAZIL DALAM SENGKETA PERDATA: Comparison of Simple Lawsuits in Indonesia and Brazil in Civil Disputes - Abiyyu Muhammad Zaki; Gandes Candra Kirana (Faculty of Law, Universitas Trisakti, 2026)
Simple lawsuit is a simplified civil dispute resolution mechanism aimed at providing a fast, simple, and low-cost judicial process. In Indonesia, this mechanism is regulated under Supreme Court Regulation Number 2 of 2015 as amended by Regulation Number 4 of 2019. Meanwhile, Brazil applies a similar concept known as the Juizado Especial Cível, which functions as a special court handling small-value civil cases through simplified and informal procedures. The problem statement is how the settlement of civil disputes is regulated within the simple lawsuit mechanism in Indonesia and Brazil. This study employs a normative legal research method using a comparative law approach. Data were collected through a literature review of laws and regulations, legal doctrines, and related academic sources. The findings indicate that although both countries share the same objective of accelerating dispute resolution, significant differences remain, particularly regarding claim value limits, the role of judges, mediation mechanisms, and evidentiary procedures. Brazil’s system is considered more accessible and flexible due to the establishment of specialized courts, while Indonesia implements simple lawsuits within the general court system with more formal procedural restrictions.